Carbonic anhydrase IV in lizard chemical signals - Marco Mangiacotti; Marco Fumagalli; Claudio Casali; Marco Biggiogera; Federico Forneris; Roberto Sacchi (Scientific Reports, 2023)
Abstract The evolution of chemical signals is subject to environmental constraints. A multicomponent signal may combine semiochemical molecules with supporting compounds able to enhance communication efficacy. Carbonic anhydrases (CAs) are ubiquitous enzymes catalysing the reversible hydration of carbon dioxide, a reaction involved in a variety of physiological processes as it controls the chemical environment of the different tissues or cellular compartments, thus contributing to the overall system homeostasis. CA-IV isoform has been recently identified by mass spectrometry in the femoral gland secretions (FG) of the marine iguana, where it has been hypothesized to contribute to the chemical stability of the signal, by regulating blend pH. Lizards, indeed, use FG to communicate by delivering the waxy secretion on bare substrate, where it is exposed to environmental stressors. Therefore, we expect that some molecules in the mixture may play supporting functions, enhancing the stability of the chemical environment, or even conferring homeostatic properties to the blend. CA-IV may well represent an important candidate to this hypothesized supporting/homeostatic function, and, therefore, we can expect it to be common in FG secretions of other lizard species. To evaluate this prediction and definitely validate CA identity, we analysed FG secretions of eight species of wall lizards (genus Podarcis), combining mass spectrometry, immunoblotting, immunocytochemistry, and transmission electron microscopy. We demonstrate CA-IV to actually occur in the FG of seven out of the eight considered species, providing an immunochemistry validation of mass-spectrometry identifications, and localizing the enzyme within the secretion mass. The predicted structure of the identified CA is compatible with the known enzymatic activity of CA-IV, supporting the hypothesis that CA play a signal homeostasis function and opening to new perspective about the role of proteins in vertebrate chemical communication.